PERAN ORANG TUA DALAM MENANAMKAN AGAMA DAN MORAL KEPADA ANAK DI TENGAH KRISIS KETELADANAN SOSIAL DI RA AL-MUJTAMA PAMEKASAN - Novie Aliva Mawardi; Abd. Rosyid (ABATATSA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Parents have a very important role in instilling religious and moral values ​​in the midst of a social role model crisis. Parents have a big responsibility in educating, caring for, and guiding their children to become moral children who are ready to live in society. The aim of this research is to describe the role of parents in overcoming the crisis of social role models at RA Al-Mujtama. The method in this research uses a qualitative approach with secondary data sources, namely journals, books and theses that support the research object and the primary data sources are from the results of interviews with the pricipal, teachers and parents, data collection techniques through observation, interviews and documentation with the principal, teachers and parents at RA Al-Mujtama. The results of this study revealed that there are four important roles of parents in instilling religious and moral values ​​in children, namely as educators, motivators, role models, and as friends. Parents need to have a high level of awareness to be able to carry out these four roles. The way to instill religious and moral values ​​starts from daily habits, such as parents teaching children to pray and recite the koran together, and also modeling polite, honest and sharing behavior with others. The obstacles parents face in instilling religious and moral values ​​in children are parents' busyness in earning money, parents who still lack religious knowledge, and the situation of the surrounding environment.